Features of Diglossic Stability in Arabic with Counterexamples - Mark Shockle (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Arabic, as a macrolanguage, represents the quintessential example of classical diglossia and remains one of the most extensively studied and well-documented cases of this linguistic phenomenon. The spoken and written varieties of Arabic have diverged over such a long period that some scholars have suggested that Arabic diglossia may have existed even before the advent of Islam. Regardless of its historical origins, various social and cultural factors have sustained Classical Arabic and Modern Standard Arabic as the prestigious language varieties. Above all, the primary force preserving this linguistic continuity for centuries has been the religio-linguistic ideology associated with Islam. This paper examines the sociolinguistic conditions and ideological factors that contribute to the stability of Arabic diglossia while also discussing several counterexamples that illustrate instances of diglossic shift.